The relationship between self-efficacy and self-care behaviors in - Bagheri saveh, mohammad iraj; -AshkTorab, tahereh; Borz Abadi Farahani, ziba; Zayeri, farid; Zohari Anboohi, sima (Advances in Nursing & Midwifery, 2013)
Abstract Background and Aim Materials and Methods R R Findings Conclusion: Keywords: Corresponding Author: Email: t_ashktorab@sbmu.ac.ir Tahereh Ashketorab. Department of Medical–Surgical Nursing, Faculty of Nursing and Midwifery. Shahid Behshti University of Medical Sciences, Tehran, Iran. Self-efficacy, Self-care behaviors, Congestive heart failure Self-efficacy and self-care behaviors in CHF patients are not at a desirable level which needs to be promoted within self-care programs. Self-efficacy, as the most important CHF-related self-care, has got a high level of importance. Therefore, self-efficacy must be reinforced especially in these patients that seem to be weaker in this domain. : The average age of patients was 64.97±13.53 years old and 55.3 percent of the samples were male. The amount of self-care behaviors by patients was moderate (average scores of 39.54) and correlated to education, place of living and disease education but its relation to age, sex, gob, marital status, disease class, ejection fraction and addiction to smoking, opium and alcohol was not statistically significant. The amount of self-efficiency of the majority of patients was moderate (average scores of 26.60) and it was also related to age, marital status, education, disease class and addiction to opium but its relation to sex, job, place of living, ejection fraction, disease education and addiction to smoking and alcohol was not statistically significant. There was a direct and strong correlation between self-efficiency and self-care behaviors (P< 0.001, r=0.623). Given that the correlation coefficient of Pearson in this study is positive and close to 1 (r = 0.623), it indicates that self-efficacy was positively correlated with self-care behaviors and its respective variance was 39%. =0.80) and test-retest (r=0.85). The data were analyzed using the SPSS software (version 16). =0.85), test-retest (r=0.80), and the reliability of the European Heart Failure self-care behaviors scale was figured by internal consistency ( : The study had a descriptive, correlational design. The method used for sampling was capitation and the study samples consisted of 150 patients under treatment referring to internal heart wards of Tohid hospital in Sanandaj. Three questionnaires were used in this study including: 1) Demographic and disease information 2) Cardiac self – efficacy Sullivan scale 3) European Heart Failure Self-care behaviors scale Second and third scales were used to record self–efficacy and self-care behaviors through interviewing each subject into private. After determining content and face validities, the reliability of the cardiac self–efficacy Sullivan scale was figured by internal consistency ( : Chronic Heart Failure (CHF) as a chronic disease demands special self-care behaviors lifelong. -Alizadeh Z (2011). [Correlation between perceived social support and self-care behaviors of patients with heart failure in hospitals affiliated with Shaheed Beheshti University of Medical Sciences and Health Services. Master Disseration of Nursing Education]. Nursing and Midwifery School.Shahid Beheshti University of Medical Sciences. (Persian). -Azarpad M (2005). [Examination the correlation between self-care behaviors and self-care needs in patients with CHF refferd to Shahid Rajaee hospital. Master Dissertation of Nursing Education].Nursing and Midwifery school.Iran University of Medical Sciences. (Persian). -Bandura A (1997).Self-efficacy: The Exercise of Control. New York: W.H.Freeman. -Chlebowy D Garvin B (2006). Social support, self-efficacy, and outcome expectations: impact on self-care behaviors and glycemic control in Caucasian and African American adults with type 2 diabetes. Diabetes Educator. 32 (5) 777- 786. -Dickson V Deatrick J Riegel B (2008). A typology of heart failure self-care management in non- elders. European Journal of Cardiovascular Nursing.7 (3) 171-181. -Gonzaleza B Lupon J Parajon T et al (2006 ). Use of the European heart failure self-care behavior scale (EHFSCBS) in a Heart Failure Unit in Spain. Revista Espanola De Cardiologia 59 (2) 166-170. -Habibolahzadeh H et al (2009). [Examination the reasons of CHF and the knowledge and function of patients in selfcare]. Scientific Magazine Of Medicine organization of Islamic Republic of Iran.19 (2)85-89. (Persian). -Heo S Moser DK Lennie TA et al (2008). Gender diffrences in and factors related to self-care behaviors: A crosssectional, correlational study of patients with heart failure. International Journal of Nursing Studies.45 (4) 1807-1815 -Jaarsma T Halfens R Senten M et al (1998). Developing a supportive educative program for patients with advanced HF within orem’s general theory of nursing . Nursing Science Quarterly.11 (2) 79-85. -Jaarsmaa T Stromberge A Martensson J et al (2003). Development and testing of the European heart failure self-care behaviour scale.The European Journal of Heart Failure.5 (3) 363-370. -Judkins C, Grady KL(2004) State of the science for cardiovascular nursing outcomes: heart failure. The Journal of Cardiovascular Nursing . 19 (3) 329-338 -Kaviani A Aghili M(1997)[Psychiatric Diseases].1 th edition.Tehran. Tabalvor publication. (Persian). -Mohammad Hassani MR Farahani B Zohouri AR et al (2010).[Self-care ability based on Orem’s theory in individuals with coronary artery disease]. Iranian Journal of Critical Care Nursing. 3 (2) 87-91. (Persian). -Morowatisharifabad M RohaniTonkaboni N (2008).[ Perceived self-efficacy in self-care behaviors among diabetic patients referring to Yazd Diabetes Research Center].Birjand University of Medical Science Joournal. 15 (4) 91-99. (Persian). - Naghib S(2010).[Correlation of self-efficiency to compliance in patients suffering from tuberculosis ,who are being trated iv health centers related to kordestan medical university.Master Disseration of Nursing Education ].Nursing and Midwifery School.Shahid Beheshti University of Medical Sciences. (Persian). -Raffeefar SH Atarzadeh M AhmadzadeAsl M et al (2005). [Educational guiedline in pharhangsara].1 th editin.Ghom Medical Sciences and Health Services University. (Persian). -Rezaee Looyeh H Dalvandi A Hosseini M et al (2008). [The effect of self-care education on quality of life in patients with CHF]. Rehabilitation. 10 (2) 21-27. (Persian). -Riegel B Vaughan Dickson V Kuhn L et al (2010). Gender -specific barriers and facilitators to heart failure self-care: A mixed method study. International Journal of Nursing Studies. 47 (7) 888-895. -Rockwell JM Riegel B (2001). Predictors of self-care in persons with heart failure.HEART & LUNG. 30 (1)18-25 -Shakibazadeh E Rashidian A Larijani B et al (2009). [Correlation between perceived self-efficacy and barriers with self care in patients diabet type 2]. Hayat. 15(4)69-78. (Persian). -Shamsi A (2011). [Correlation between dimensions of self-efficacy and dimension of fatigue in faculity members in school of Nursing & midwifery. Master Disseration of Nursing Education]. Nursing and Midwifery School Shahid Beheshti University of Medical Sciences (Persian). - -Shojafard J Nadrian H Baghiani Moghadam MH et al (2009). Effects of an educational program on self-care behaviors and its perceived benefits and barriers in patients with Heart Failure in Tehran. Payavard Salamat.2 (4) 43-55 - Shojaee F Asemi S Najaf Yarandi A et al (2006). [Examination the correlation between self-care behaviors with quality of life in patints with CHF].Iranian Nursing Magazine.18 (44) 49-56 (Persian). - Shojaee F Asemi S Najaf Yarandi A et al (2009). [Self-care behaviors in patients with CHF]. Payesh Faslnameh. 8 (4) 361-369. (Persian). - Thomas LK Sargent RG Michels PC et al (2001). Identification of the factors associated with compliance to therapeutic diet in older adults with end stage renal diseases. Journal of Renal Nutrition . 11(2). 80-89 These patients in order to control the problems of this disease need self-care behaviors. So, recognition of these behaviors and encouragement patients to participate and acceptance the responsibility of doing these behaviors lead to control the problems of this disease. Self-efficacy is a basis for promoting self-care behaviors in CHF which play a major role in treatment and control of the complications. Self-efficacy is proposed as a concept of social learning theory and a construct of health belief model, particularly when the model is used for predicting simple lifestyle changes in chronic diseases. This study was designed and carried out to determine the status of this construct and its related factors and also, its correlation with self-care behaviors among patients with CHF.